The socioeconomic returns to citizenship: A randomized controlled trial - Jens Hainmueller; Elisa Cascardi; Michael Hotard; Rey Koslowski; Duncan Lawrence; Vasil Yasenov; David D. Laitin (Proceedings of the National Academy of Sciences, 2026)
Based on observational studies, conventional wisdom suggests that citizenship carries economic benefits. We leverage a randomized experiment from New York where low-income registrants with permanent residency who wanted to become citizens entered a lottery to receive fee vouchers to naturalize. Voucher recipients were about 36 p.p. more likely to naturalize. Yet, we find no discernible effects of access to citizenship on multiple economic outcomes, including income, credit scores, access to credit, financial distress, and employment. Leveraging a multidimensional immigrant integration index, we similarly find no measurable effects on noneconomic integration. However, we do find that citizenship reduces fears of deportation. Explaining divergence from past studies, our results also reveal evidence of positive selection into citizenship, suggesting that observational studies are susceptible to selection bias.